Evaluasi User Experience Pada Game Playerunknown’s Battlegrounds (Pubg) Mobile Menggunakan Metode Heuristic Evaluation - Idria Maita; Danil Risaldi; Megawati; Febi Nur Salisah (The Indonesian Journal of Computer Science, 2024)
Pubg Mobile game is a game developer from "Tencent Games", Pubg Mobile was released on February 9, 2018. The genre of this game is Battle royale, where players can play with 100 people at once online. There are several negative reviews from Pubg Mobile game users, namely, character bugs often occur during the game, often force close on 3 GB RAM smartphones and loading into the game is very long so that users are very uncomfortable when using it. This study uses the Heuristic Evaluation method as a measurement of user experience. This study aims to evaluate the user experience in the Pubg Mobile game application using the Heuristic Evaluation method. The results of this study indicate that the Visibility Of System Status variable gets a total value of p1 75.6%, total p2 72.9%, total p3 75.6% with the status "Good", Match Between System and Real World gets a total value of p1 64.8%, total p2 75.6%, total p3 72.9% with the status "Good". User Control And Freedom gets a total value of p1 72.9%, total p2 75.6%, with the status of "Good", Consistency And Standards gets a total value of p1 51.3%, total p2 70.2% with the status of "Not Good", Error Prevention gets a total value of p1 70.2%, total p2 70.2%, with the status of "Good", Recognition Rather Than Recall gets a total value of p1 72.9%, total p2 72.9%, with the status of "Good", Flexibility And Efﬁciency Of Use gets a total value of p1 56.7%, with the status of "Quite Good", Aesthetic And Minimalist Design gets a total value of p1 78.3%, with the status of "Good", Help User Recognize, Diagnose And Recover From Errors gets a total value of p1 78.3%, with the status of "Good", and the last variable Help And Documentation gets a total p1 78.4%, with the status of "Good". It is necessary to make improvements or enhancements to the Consistency And Standards variables to get better values ​​than before.